1998
DOI: 10.1099/00207713-48-1-295
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the Saccharomyces cerevisiae group based on polymorphisms of rDNA spacer sequences

Abstract: Phylogenetic analysis of the Saccharomyces cerevisiae group based on polymorphisms of rDNA spacer sequencesRobert M on t roc her, M a r i e-C h r ist i ne Verner, JerBme B r io I ay,2 Christian Gautier2 and Roland Marrneissel The phylogenetic relationships between species of yeasts assigned to the Saccharomyces sensu stricto group, which includes Saccharomyces cerevisiae and Saccharomyces bayanus, were studied together with Saccharomyces pastorianus and Saccharomyces paradoxus. The ex per i mental approaches u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 32 publications
5
45
0
2
Order By: Relevance
“…This is in accordance with the rather isolated position of Sacch. paradoxus when compared with the other members of the "cerevisiae" cluster based on PCR-RFLP and ITS sequence analyses as reported by Montrocher et al 8 In addition, the Saccharomyces sensu stricto group could easily be differentiated from the Saccharomyces sensu lato group when comparing band patterns after Sau 3A1 digestion (Fig. 4, Table IV).…”
Section: '32'097-327mentioning
confidence: 74%
See 1 more Smart Citation
“…This is in accordance with the rather isolated position of Sacch. paradoxus when compared with the other members of the "cerevisiae" cluster based on PCR-RFLP and ITS sequence analyses as reported by Montrocher et al 8 In addition, the Saccharomyces sensu stricto group could easily be differentiated from the Saccharomyces sensu lato group when comparing band patterns after Sau 3A1 digestion (Fig. 4, Table IV).…”
Section: '32'097-327mentioning
confidence: 74%
“…In recent times, there have been a number of reports describing the application of molecular genetic tools for the differentiation and characterisation of yeasts used in industrial fermentation 2,3,4,7,8,9,11 . Data from these studies show that RFLP patterns allow recognition of individual species as well as individual strains within a species.…”
mentioning
confidence: 99%
“…The 840-bp fragment corresponds in size to the region encompassing S. cerevisiae chromosome 12 coordinates 455966-455123 comprising 394 bp of ITS1, 158 bp of 5.8S rDNA, and 288 bp of ITS2. To confirm the Saccharomyces origin of the 840-bp product, we designed new primers ITS5 and ITS6, internal to the 840-bp S. cerevisiae ITS1-5.8S rDNA-ITS2 sequence, which would specifically amplify sequences belonging to the genus Saccharomyces (Montrocher et al 1998). Amplifications of the extracted DNA with the primer pair ITS1-ITS6 produced a band of 320 bp, amplification with ITS5-ITS4 produced a band of 650 bp, and amplification with ITS5-ITS6 produced a band of 130 bp.…”
Section: Resultsmentioning
confidence: 99%
“…Based on rDNA sequences and molecular karyotyping, the species was divided into two subgroups, 'bayanus' and 'uvarum' (Nguyen and Gaillardin, 1997;Gouliamova and Hennebert, 1998;Montrocher et al, 1998;Rainieri et al, 1999;Naumov et al, 2000a), which were later identified by genetic hybridization analysis as two varieties (Naumov, 2000 The growing interest in studying S. bayanus species is connected not only with its possible role as a contributor to the S. carlsbergensis genome but also with its significance as a new gene pool for the cultured Saccharomyces yeasts. The specific ecological niche of S. bayanus var.…”
Section: Introductionmentioning
confidence: 99%